Karakteristik Pasien dengan Keputusan Pembelian Jasa Layanan Kesehatan Gigi dan Mulut - Susilawati Susilawati; Nyoman Anita Damayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to analyze the relationship between patient characteristics, including gender, age, education level, occupation, and dental health values ​​, with the decision to purchase dental and oral health services. The research method used in this research is analytic observational with a cross-sectional study design. The results showed that most of the dental clinic patients were female as much as 73.8%, adult age was 82.2%, middle education was 60.7%, students were 68.2%, and the value of moderate dental health was 55, 1%. There is a significant relationship between the amount of dental health (p-value = 0.024) and the decision to purchase dental and oral health services, while gender, age, education level, and occupation show no significant relationship. In conclusion, patient characteristics in dental health values ​​determine patients in making decisions related to purchasing dental and oral health services. Keywords: Patient Characteristics, Purchase Decisions, Dental Health